2010
DOI: 10.1590/s1519-69842010000400020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of indomethacin on the regenerative process of the tail fin of teleost: morphometric and ultrastructural analysis

Abstract: When partially amputated or severely injured, teleost fins suffer a regenerative process called epimorphic regeneration characterised by the following stages: the formation of a multistratified epidermal layer, the disorganisation and distal migration of multipotent mesenchymal cells, the proliferation of these cells in order to form the blastema, continuous proliferation of distal blastema to facilitate the growth, and differentiation of the proximal blastema in order to restore its lost structure. The regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Extensive molecular genetic studies on the formation and function of actinotrichia have been conducted in zebrafish. Several studies using transmission electron microscopy (TEM) have shown that actinotrichia are distributed between the basement membrane just below the basal epithelial cells and mesenchymal cells ( Wood and Thorogood, 1987 ; Böckelmann and Bechara, 2010 ). In zebrafish larva with Col1a1a and Col2a1b function inhibited using morpholino antisense oligos, actinotrichia production is inhibited and the fin fold growth is defective ( Durán et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive molecular genetic studies on the formation and function of actinotrichia have been conducted in zebrafish. Several studies using transmission electron microscopy (TEM) have shown that actinotrichia are distributed between the basement membrane just below the basal epithelial cells and mesenchymal cells ( Wood and Thorogood, 1987 ; Böckelmann and Bechara, 2010 ). In zebrafish larva with Col1a1a and Col2a1b function inhibited using morpholino antisense oligos, actinotrichia production is inhibited and the fin fold growth is defective ( Durán et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%